AWE-05 Case series of per-oral endoscopic pyloromyotomy in patients with refractory gastroparesis: a single centre experience. Issue 2 (June 2019) - Gunasingam, Nishmi; Patel, Mehul; Gulati, Shradda; Haji, Amyn; Hayee, Bu'Hussain
Abstract : Introduction: Gastroparesis (GP) is a disorder evidenced by delayed gastric emptying in the absence of mechanical obstruction, commonly idiopathic or secondary to diabetes mellitus. G-POEM has been used to treat refractory gastroparesis and we present our initial experience with this novel endoscopic technique. Methods: All patients undergoing G-POEM for refractory GP from May 2018 onwards were included, with data extracted from the hospital electronic patient record. Procedures were performed by one endoscopists at our centre with experience in submucosal endoscopy. Efficacy at 3 months was assessed by reduction of symptom score (Gastroparesis Cardinal Symptom Index; GCSI), with secondary considerations including technical success, procedural complications, hospital length of stay and hospitalisations after treatment. Results: 10 patients (10F; mean age 40.3± 15.4 y) were included (5 diabetic, 5 idiopathic). Mean duration of disease was 9.5± 5.6 y, with 4 months median duration of follow-up post-procedure. 6 patients had previous treatment with botulinum toxin, and one gastric electrical stimulator. Technical success was achieved in all cases while, at 3 months, 8 had improvement total GCSI (mean scores 3.978 vs 2.076 (p=0.008)) and each GCSI subtype score: nausea and vomiting (3.63 vs 1.70, p=0.012); fullness (4.30 vs 2.30, p=0.012); bloating (4 vs 2.22, p=0.28). Mean hospital stay was 9± 13 d, with 5 patients staying less than 4 days and two with prolonged admission. One significant adverse event was recorded: abdominal collection around the myotomy site requiring a prolonged hospital admission of 18 days for intravenous antibiotics in one patient. Only one patient required hospitalisation for gastroparesis symptoms after their G-POEM procedure (this was the same patient who did not achieve clinical success with reduction in their GCSI scores). Conclusion: G-POEM is a promising therapeutic treatment for patients with refractory GP, with significant improvement in symptoms and, in our cohort a dramatic reduction in the need for hospitalisation in short-term follow up. A European sham-controlled study is under way and longer-term data are required to confidently determine its role in the management of such a challenging condition.